An underappreciated dimension of human trafficking: battered and trafficked women and public policy - Miller, Mark J. (Human rights review, 2011)
Both domestic violence and trafficking in humans pose serious problems worldwide. However, there are differences in the ways in which battered immigrant women and trafficked immigrant women are responded to by governmental agencies in Greece and in the USA. Trafficking in humans has been securitized, that is, framed as an issue linked to international security risk. As such, countries that do not take legal action to stop human trafficking could face US sanctions such as loss of United States military and economic assistance. Under significant international pressure, Greece, since 2002, passed a law that criminalized trafficking in humans and took necessary steps for providing protection and assistance to trafficked victims. Nevertheless, domestic violence and battered women remain silent in Greek society, and the availability of services to victims of domestic violence has eroded. We argue that, due to different issue framing of victims of trafficking and battered women, the connection of trafficking in humans to national security fosters different legal protection outcomes. The comparison of battered immigrant women and trafficked victims between Greece and the USA reveals significant differences in protection of battered immigrant women in the Organization for Economic Cooperation and Development (OECD) area. This article elucidates why there are public policy differences within OECD states that all grant a priority to prevention of human trafficking.